Performing an Effective Business Process to Overcome Defect and Delay in Manufacturing Sportswear Product by Using DMAIC Approach - Panjeraino, Haykal Satria; Farmaciawaty, Desy Anisya (Journal of Innovation, Business and Entrepreneurship, 2019)
Sport as an industry has been growing so fast in Indonesia market, make so many of sportswear brand come and rise in this industry. For that, every brand have to make sure that every aspect of their business are work with improvement if they want to survive on this environment of tough competition. One of the most important aspects is operational, where the sportswear product will directly use by the customer. If the product is not good, the brand either.This research discusses the way to reach operational excellence in the company as one of the important aspects to run a business. Aims of this research is to implement the improvement of production lead time in one of the sportswear SME that apply ‘Made by Order’ type of production. Six sigma approach will be used on this research to improve the operational aspect in the company, which was initially comes from the 1990s in a manufacturing company for manufacturing and transactional processes. Six Sigma has proven successful in decreasing lead time or variation, bring up customer satisfaction, and make profit significantly increasing.One of the Six Sigma tools that will use on this research is DMAIC (Define, Measure, Analyse, Improve, and Control), a step-by-step to find the critical process in order to identified and remove the bottle neck, so the production lead time will be reduced with the good quality on production result. In Define step, defined the problem which occur in Panjers. Then the next step is Measure, in this step measured the losses of Panjers and calculate the lead time by explaining all the business process. After knew the losses and already knew the lead time, next step is Analysed the bottleneck and the cause of bottleneck by using fish bone diagram. Then knew the root cause of the problem and gave the solution for improve the business process and decrease lead time. To maintain the improved business process, the next step is controlling, which will use PDCA (Plan, Do, Check, and Act) tools for this step.Keywords : Six Sigma, DMAIC, Business Process, Made-by-Order, Production Lead Time